Éric Weil and Hegel’s Philosophy of right - Canivez, Patrice (Argumentos - Revista de Filosofia, 2022)
This article deals with the relationship of Eric Weil's political thought with Hegel's Philosophy of Law, based on two texts by Eric Weil: “Hegel and the Concept of Revolution” and “The Philosophy of Law and the Hegelian’s Philosophy of History”, translated and published in Brazil in a volume entitled Hegel e Nós. The article analyzes these two texts. The first shows how the Hegelian concept of revolution focuses more on the revolutionary situation - its problematic - than on revolution as an event. This allows us to apprehend fundamental distinctions in Éric Weil, such as the difference between revolt and revolution and as two modalities of revolution: one based on a mass movement, the other that a responsible government must implement to deal with the necessary changes before they are imposed by a violent revolt. The second text places the Philosophy of Law in the Hegelian theory of history. This allows us to differentiate between Hegel's theoretical attitude, from which an essentially speculative understanding of history proceeds, and Eric Weil's approach, which emphasizes action. From the analysis of two texts and according to the historical context in which Éric Weil develops his own thought, the article offers elements of comparison and differentiation between the Hegelian Philosophy of Law and Political Philosophy published by Eric Weil in 1956.